1982
DOI: 10.3354/meps008009
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton Biomass and Production in a Southern Benguela Kelp Bed System

Abstract: Seasonal variation in phytoplankton biomass and production in the vicinity of a Southern Benguela kelp bed is studied in relation to the upwelling cycle. Mean phytoplankton biomass was estimated as 56 mg chl a m -2 and phytoplankton production as 1.13 kg C m-'yr-' The top 10 m of the 20 m deep water column monitored contained 83 % of the b~omass and 76.5% of the production. Daily and seasonal variations in phytoplankton are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1983
1983
1996
1996

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…The standing stocks of phytoplankton and the primary production in the coastal waters of the Cape Peninsula have been studied by Brown (1981), and more recently near to kelp beds by Carter (1982). The chlorophyll a concentrations recorded by Brown (1981) at Robben Island in Table Bay and at Oudekraal are shown together with values recorded by Seiderer (1983) in Table 1.…”
Section: Standing Stocks Of Phytoplanktonmentioning
confidence: 94%
“…The standing stocks of phytoplankton and the primary production in the coastal waters of the Cape Peninsula have been studied by Brown (1981), and more recently near to kelp beds by Carter (1982). The chlorophyll a concentrations recorded by Brown (1981) at Robben Island in Table Bay and at Oudekraal are shown together with values recorded by Seiderer (1983) in Table 1.…”
Section: Standing Stocks Of Phytoplanktonmentioning
confidence: 94%
“…Previous studies have shown that particulate and chlorophyll concentrations decline to very low levels during upwelling when offshore winds move surface waters away from the coast (Field et al 1980, Carter 1982, Brown 1984, Brown & Field 1986. These data were calculated from water samples taken at the outer edge of the Oudekraal kelp beds.…”
Section: Particulate Loadmentioning
confidence: 99%
“…Carter 1982. Furthermore, Carter (1982) expressed reservations about annual phytoplankton production estimates because of the accumulated errors in extrapolating daily and seasonal rates to annual rates in such a variable system. Brown & Field (1985) described largescale die1 fluctuations in phytoplankton productivity over 4 d periods at different times of the year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary production off the west coast of southern Africa varies significantly both spatially and over seasonal and shorter time scales (Andrews and Hutchings 1980;Brown 1984;Carter 1982;Brown and Field 1985). Investigations by Brown and Hutchings (1985) have led to a better understanding of the factors regulating primary production in the Cape Peninsula upwelling system, variations of nutrients and light in the upper mixed layer being considered the major environmental regulators of primary production.…”
mentioning
confidence: 99%